The Relevance of Reward and Punishment in the Book of Asy Syamail Al-Muhammadiyah to the Discovery Learning Model for Adults - Tohirin Tohirin; Ahmad Ridla Syahida (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research aims to reveal the educational values contained in the hadiths regarding reward and punishment in the book Asy-Syamail Al-Muhammadiyah by Imam Tirmidzi, and to analyze their relevance to the Discovery Learning model for adults (andragogy). The methodology employed is a qualitative approach using descriptive-analytical methods through a systematic literature review and conceptual analysis of both explicit and implicit hadith texts. The results indicate that the book provides authentic information regarding the Prophet Saw's practice of rewards, such as praise, provision of facilities, and enthusiasm, while punishment was administered through prohibitions, reprimands, warnings, or educational actions. These findings confirm a strong relevance between the reward and punishment methods exemplified by the Prophet and the operational steps of Discovery Learning, where appropriate motivation and consequences are essential to support the independence of adult learners in exploring and discovering concepts independently within the Merdeka Curriculum framework. The integration of these prophetic values significantly contributes to the development of a learning model that addresses not only cognitive aspects but also the formation of character or insan kamil.